Madhva (1198-1278). Pluralism, realism and theism in indian philosophy - Tola, Fernando; Dragonetti, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
After some remarks on the Veda¯ nta philosophical school, the context of Madhva’s thought, the article develops Madhva’s Pluralism and Realism. His pluralism is based on the notions of «difference» and «own nature», and considers God, souls and matter as real and eternal entities, essentially different from one another. The article offers Sanskrit and Spanish translations of a small treatise of Madhva, which provides a schematic but clear exposition of Madhva’s ontology. Three themes are highlighted: the unicity of God (Vishn. u), the absolute power of God and predestination. The article presents other texts of Madhva, which describe Vishn. u’s nature and His supreme qualities. Finally the article deals with Madhva’s predestination doctrine. Some of his texts maintain a despotic-fatalistic conception of predestination; and others, that modify the previous ones present a conception inspired by the idea of God’s Justice and Goodness. The article ends with some remarks on knowledge and devotion as a means to reach God.
Keywords: Madhva; realism; eternity; pluralism; God; souls; matter; predestination; knowledge; devotion